P PENGERTIAN, KEDUDUKAN, CAKUPAN, TUJUAN PERBANDINGAN PENDIDIKAN DAN HISTORI SERTA LANDASAN HISTORI PENDIDIKAN DI INONESIA - Indah Siti Nurhalizah; Pitriani; Saipul Annur; Ade Rosad (LP2M IAIN Sultan Amai Gorontalo, 2025)
Comparative education studies examine the similarities, differences, and factors influencing the education systems of various countries. This study is crucial for understanding the dynamics of global education and supporting national policy development. The primary focus is on identifying similarities and differences in education systems and understanding the historical and contextual factors that shape these policies. This research analyzes relevant national and international literature and journals, including the history of education in Indonesia. The results demonstrate that comparative education is not only analytical but also helps adapt best practices to Indonesia's social, cultural, and political context. Aspects examined include educational philosophy, curriculum, learning methods, policies, educational structures, and external factors such as economics and culture. From pre-colonial times to the reform era, education plays a role in strengthening cultural values, developing human resources, and shaping national identity. This study emphasizes the importance of integrating lessons from other countries while maintaining Indonesia's distinctive characteristics for effective and sustainable policy.